Health Professions Education Research and the Institutional Review Board. Issue 2 (March 2016) - Heflin, Mitchell T.; DeMeo, Stephen; Nagler, Alisa; Hockenberry, Marilyn J.
Abstract : The growth in health professions education (HPE) and a desire on the part of nurse and medical educators to disseminate their work have raised important questions about the ethical conduct of education research. At the center of the debate is the institutional review board (IRB) and its proper role in the oversight of HPE research. This article examines the IRB process and types of reviews for education research and presents an Education Project Summary Template to use for IRB reviews.